In vitro erythrocyte membrane stabilization properties of Carica papaya L. leaf extracts - Ranasinghe, Priyanga (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Carica papaya L. fruit juice and leaf extracts are known to have many beneficial medical properties. Recent reports have claimed possible beneficial effects of C. papaya L. leaf juice in treating patients with dengue viral infections. This study aims to evaluate the membrane stabilization potential of C. papaya L. leaf extracts using an in vitro hemolytic assay. MATERIALS AND METHODS: The study was conducted in between June and August 2010. Two milliliters of blood from healthy volunteers and patients with serologically confirmed current dengue infection were freshly collected and used in the assays. Fresh papaya leaves at three different maturity stages (immature, partly matured, and matured) were cleaned with distilled water, crushed, and the juice was extracted with 10 ml of cold distilled water. Freshly prepared cold water extracts of papaya leaves (1 ml containing 30 μl of papaya leaf extracts, 20 μl from 40% erythrocytes suspension, and 950 μl of phosphate buffered saline) were used in the heat-induced and hypotonic-induced hemolytic assays. In dose response experiments, six different concentrations (9.375, 18.75, 37.5, 75, 150, and 300 μg/ml) of freeze dried extracts of the partly matured leaves were used. Membrane stabilization properties were investigated with heat-induced and hypotonicity-induced hemolysis assays. RESULTS: Extracts of papaya leaves of all three maturity levels showed a significant reduction in heat-induced hemolysis compared to controls (P < 0.05). Papaya leaf extracts of all three maturity levels showed more than 25% inhibition at a concentration of 37.5 μg/ml. The highest inhibition of heat-induced hemolysis was observed at 37.5 μg/ml. Inhibition activity of different maturity levels was not significantly (P < 0.05) different from one another. Heat-induced hemolysis inhibition activity did not demonstrate a linear dose response relationship. At 37.5 μg/ml concentration of the extract, a marked inhibition of hypotonicity-induced hemolysis was observed. CONCLUSION: C. papaya L. leaf extracts showed a significant inhibition of hemolysis in vitro and could have a potential therapeutic effect on disease processes causing destabilization of biological membranes.